Ciência e experiência: para uma interpretação da fenomenologia do espírito de Hegel - Barbosa, Alexandre de Moura (2007)
This research has as purpose the clarification of a classic controversy in the Hegel’s interpretation concerning the position and of the direction of the Phenomenology of the Spirit in the system. For this, to analyze the relation between the Experience and Science, since the Phenomenology is a science of the experience. Of one it has left if it has the interpretation of Haering on this question: the Phenomenology would be or an introduction or part of the system? This interpretation was developed by Hyppolite in “Gênese and structure of the Phenomenology of spirit of Hegel”. For Hyppolite, the Phenomenology would be a paidéia in its direction of learning; a learning of the soul to the spirit, the conscience to the absolute one. This position is critical later for Labarrière and Otto Poeggeler, for these the genetic interpretation of Haering and Hyppolite is arbitrary. One third interpretations that would bring light to this quarrel is of Bourgeois in “Felt and intention of the Phenomenology of the spirit”, it places in question the interpretation of Hyppolite concerning the purpose and of the conscience of it carries through the movement, placing on suspicion the interpretation of the Phenomenology of the spirit as a paidéia. To decide this series of difficulties and interpretation problems, I opted to approaching the Hegel’s solution of the platonic solution in the Mênon. The central relation between Science and Experience would be the category of the remembrance (Er-innerung).